Metacognition Skill Exploration in Six Developing Countries: A Systematic Literature Review Towards Advancing Learning Quality - Anisa Puteri; Didit Ardianto (Universitas Negeri Semarang, 2023)
This study was conducted to analyze the literature related to the role of metacognition in science learning in six developing countries in an effort to improve the quality of learning. The objectives of this study include: 1) to explore the role of metacognition as a learning strategy applied to science learning; 2) to explore the role of students' metacognition skills in science learning. 3) knowing the role of metacognition in science learning to improve the quality of science learning. The benefit of this research is to facilitate researchers in obtaining literature that is suitable for analysis related to the research title to be carried out by researchers. The method of this research is to use the Systematic Literature Review (SLR) method, which consists of 4 steps, including identification, screening, eligibility, and inclusion. The results of this study are obtained from as much as six pieces of literature that are suitable for analysis. The results of the analysis of this article include: 1) Some parts of the country applying metacognition strategies in science learning are proven to be able to improve 21st century skills and also concept understanding. 2) Some parts of the country apply several innovative learning models that are able to improve students' metacognition skills. The level of education that is widely used in the research studies reviewed is 40% at the junior and senior high school level and 20% at the university level. It is expected that this research will emphasize common patterns, challenges, and opportunities in using metacognitions skills in various science education contexts by gathering information from various relevant studies.